Professional development : the dynamics of success - Wilkes, Mary.; Crosswait, C. Bruce (Orlando, Fla. : HBJ Media Systems Corp., 1984)
This book is organized around the premise that the techniques and personal qualities students need to find the best possible job in a particular field are identical to those that they must develop and refine in order to become effective and promotable employees. The book is divided into five parts. Part One: Starting Out Right. Part Two: Projecting Your Image. Part Three: Working With Others. Par Four: Planning For Success. Part Five: Moving Up the Ladder
Includes bibliographies and index.
rpm 06/04/2018, ijb 10/04/2019
Loans
Keywords: Success in business; Grooming for men; Beauty, Personal; Interpersonal relations